2004
DOI: 10.1590/s1517-83822004000100006
|View full text |Cite
|
Sign up to set email alerts
|

SDS-Page and numerical analysis of Candida albicans from human oral cavity and other anatomical sites

Abstract: The aim of the present research was to evaluate the protein polymorphism degrees among forty-eight C. albicans isolates from fourteen anatomical sites of clinical patients by polyacrylamide gel electrophoresis (SDS-PAGE) and numerical analyzes, in order to identify subspecies and their similarities in some infectious niches. Cell cultures were grown in YEPD medium, collected by centrifugation, and washed in cold saline solution. The whole-cell proteins were extracted by cell disruption using glass beads and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The efficacy of use of SDS-PAGE has also been described in aspergillosis in bronchogenic carcinoma [ 7 ]. Rodrigues et al [ 8 ] reported the use of SDS-PAGE for typing of C. albicans isolates. They found this method to be important for characterizing the yeast for epidemiological and taxonomic purposes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of use of SDS-PAGE has also been described in aspergillosis in bronchogenic carcinoma [ 7 ]. Rodrigues et al [ 8 ] reported the use of SDS-PAGE for typing of C. albicans isolates. They found this method to be important for characterizing the yeast for epidemiological and taxonomic purposes.…”
Section: Discussionmentioning
confidence: 99%
“…The SDS-PAGE has been reported for epidemiological typing of Klebsiella spp. [ 6 ], aspergillosis [ 7 ], and C. albicans [ 8 ]. Ying et al [ 9 ] indicated that the fluconazole resistance of C. albicans has overexpression of ERG11 gene.…”
Section: Introductionmentioning
confidence: 99%
“…However, in hosts predisposed to candidiasis, for example very low birth weight, immunosupressive, antibiotic, and cytotoxic therapies, diabetes mellitus , organ transplant, tumors, immunocompromised patients affected by AIDS and others, these yeasts may act as pathogens. Commensal Candida species normally inhabit in the oral, nasal and aural cavity, vaginal canal, rectum, and gastrointestinal tract of host may begin the infectious process ( Diaz-Guerra et al , 1997 ; Hellstein et al , 1993 ; Miyasaka et al , 2008 ; Oliveira et al , 2011 ; Rodrigues et al , 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…While various studies have recommended the SDS‐PAGE as a useful technique for discriminating different Candida species, particularly C. albicans (Rosa et al , 2000; Boriollo et al , 2003; Rodrigues et al , 2004), little information is available on pertinent literature concerning the use of this technique for identification of C. dubliniensis . Multilocus enzyme electrophoresis (MLEE) and SDS‐PAGE were recently used to separate C. albicans and C. dubliniensis into different taxa (Rosa et al , 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The sodium dodecyl sulfate‐polyacrylamide gel electrophoresis (SDS‐PAGE) has emerged as one of the most versatile and inexpensive techniques for the separation and resolution of bacterial proteins that may be used for the establishment of the phenotypic variability and relationship within species (Kersters, 1985). Many studies have been used this technique for the identification of important strains (Cunningham and Noble, 1989; Rosa et al , 2000; Boriollo et al , 2003; Rosa et al , 2003; Rodrigues et al , 2004). The comparison of electrophoretic protein patterns has satisfactory taxonomic resolution, which may be applicable to the level of species, subspecies and biotypes (Kersters, 1985).…”
Section: Introductionmentioning
confidence: 99%